The reverse mortgage: Consumer attitudes - Iwona Olejnik; Sylwester Białowąs (Economic and Environmental Studies (E&ES), 2017)
The main goal of this article is to describe the attitudes towards the reverse mortgage (RM) as one of the options for acquiring additional financial resources by those who have finished their professional activity and retired. The article reports the results of our own quantitative research. The study uses data obtained from representative quantitative research conducted in 443 households in the Wielkopolska region in 2015. The research used the interviewer-led paper-and-pen interview method. The tool was a standardized interview questionnaire with a random research sample. The results of the research show that the representatives of households present a very low level of awareness and knowledge of the reverse mortgage and therefore they do not accept this way of securing one's old age. The most important factors which could encourage consumers to use the RM include the need for additional funds to cover the costs related to unexpected health problems, the lack of funds for basic supplies or no relatives to receive one's property as a bequest.
Keywords: D14; D64; 330; reverse mortgage; consumer attitudes; consumer research